Strategi kampanye kreatif pengolahan sampah di permukiman padat penduduk - Aryo Bayu Wibisono; Mike Nur Kartika Sari; Andhika Putra Pradana; Satriansyah Akhlaqul Karima; Ibrahnovan Suly Trizky Darma; Ardanny Nanda Saputra (Universitas Riau, 2020)
Cleanliness and waste management were common problems in city planning. The factors of the city's problems have been a varieticalistic discovery, ranging from flooding to a health factor from an unclean environment. The waste management in Surabaya is good enough but not all equally equal, especially in suburbs. This overcrowding undermines waste management, whereas Surabaya has already created a clear path to organizing the waste until mode of bus transportation that the payment based in exchange waste. It is considering it has not been able to enable people in suburbs to understand and implement the discipline on waste management. To bring the people in diciplines requires interesting methods, and motivate the people to do so. In the scholarly of design visual communication this method is called a social campaign, the objective in this research of this social campaign, to make the most nonessential organic and unorganic waste to be usefull. Data are taken from coastal area in Surabaya specifically in Tambak Wedi, Kenjeran. The population density and unclean enviroment in this area become a proper place to study. The methods used in this study are qualitative, with observational approaches to people, social experiment trials and socialization activities. This research is an applied public study, whose hope through this research that people are able to change their habits and understand about waste management